The Influence of Online Shopping Convenience on Consumer Loyalty in Social E-Commerce: A Study of Tiktok Shop Using Linear Regression Methodology - Jodhi Caster (APPS Publications, 2023)
Purposes - The primary purpose of this study is to examine the influence of online shopping convenience on consumer loyalty within the social commerce platform TikTok Shop. The research seeks to explore how ease of transactions and user interface impacts consumer retention and satisfaction in the digital marketplace. Methodology - A quantitative research design was employed, utilizing a survey method to collect data from 77 respondents who frequently use TikTok Shop. The survey measured the convenience of online shopping as the independent variable and consumer loyalty as the dependent variable. Data were analyzed using multiple linear regression to determine the significance and strength of the relationship between the two variables. Findings - The results indicate a significant positive relationship between online shopping convenience and consumer loyalty in TikTok Shop. The linear regression model reveals that increased shopping convenience leads to higher consumer loyalty, with the model explaining 59.3% of the variance in loyalty. Features such as ease of navigation and a user-friendly interface were identified as key factors in enhancing consumer retention. Novelty - This study contributes to the growing literature on social commerce by specifically focusing on the convenience of online shopping as a predictor of consumer loyalty in the context of TikTok Shop, an area that has been relatively underexplored in prior research. Research Implications - The findings suggest that e-commerce platforms, particularly social commerce like TikTok Shop, should prioritize optimizing the shopping experience to improve consumer loyalty. This study provides practical insights for businesses to enhance user engagement and retention through improved convenience features.